SARS-COV-2 research in chemical toilets at a regional event, Mato Grosso do Sul, Brazil - Santos, Carolina Rangel de Lima; Silva, Carmem Cícera Maria da; Pussi, Kamily Fagundes; Ribeiro, Vinicius Oliveira; Konradt-Moraes, Leila Cristina; Lacerda Junior, Valdemar; Neitzke-Abreu, Herintha Coeto (Brazilian Journal of Production Engineering, 2025)
SARS-CoV-2, which is responsible for COVID-19, is transmitted mainly by respiratory droplets, and wastewater studies have also shown the presence of the virus. Chemical toilets are used in many places without a sewage collection system and contain deodorizing substances to reduce bad odor and inhibit microorganisms. The objective of this study was to investigate SARS-CoV-2 RNA in samples from chemical toilet tanks used in a public event in the city of Itaporã/Mato Grosso do Sul. A cross-sectional study was carried out from September 8 to 11, 2022, the composite samples were carried out at the end of each day of the event, totaling four samples collected in 38 chemical toilets. RNA was obtained and subjected to RT-qPCR. The samples contained a large amount of organic matter. No samples were positive on RT-qPCR. The environmental deodorant used in the tanks has benzalkonium chloride as its active ingredient. The deodorant used is believed to have inactivated the SARS-CoV-2 virus and degraded its RNA.
Keywords: Epidemiological Monitoring Wastewater-Based; COVID 19 Virus Infection; Benzalkonium Chloride.